A Review on Biosensors and Their Applications in Food and Beverage Industry - Jumal, J.; Othman, S. S. (Universiti Sains Islam Malaysia, 2024)
The foremost challenge in food and beverage industry is the need to develop quick and cost effective tools in the detection of contaminants, toxins, non-Halal components and pathogens in the food. For this reason, biosensor is one of the best tool to detect and verify the existence of those components. They are modern analytical devices which consist of bio-receptor, transducer and signal processing to produce specific reaction when in contact with a specific component. Biosensors are recently gaining much interest and widely used in analysis of bio-materials for better understanding of their bio-compositions, structures and functions by converting biological responses into electrical signals. In this review, various biosensors reported in the literatures for the detection of pork in food, detection of alcohol in fermented beverages, monitoring of fructose level and detection of harmful contaminants in dairy products are summarized, highlighting their principles, advantages, and limitations together with their simplicity, sensitivity, and multiplexing capabilities.